Diacronia e diatopia delle pratiche purificatorie per omicidio: il caso di Oreste - Luca Pucci (Otium, 2017)
The main goal of this paper is to examine some traditions about Orestes’ purification in Greek mainland (Arkadia, Troizen, Gytheium, Keryneia), in order to demonstrate two aspects: the diachronic and diatopic variety of mythical traditions about purification for homicide and the position of Delphi in the purification processes.